Salinity Tolerance Turfgrass: History and Prospects - Md. Kamal Uddin; Abdul Shukor Juraimi (The Scientific World Journal)
Land and water resources are becoming scarce and are insufficient to sustain the burgeoning population. Salinity is one of the most important abiotic stresses affecting agricultural productions across the world. Cultivation of salt-tolerant turfgrass species may be promising option under such conditions where poor quality water can also be used for these crops. Coastal lands in developing countries can be used to grow such crops, and seawater can be used for irrigation of purposes. These plants can be grown using land and water unsuitable for conventional crops and can provide food, fuel, fodder, fibber, resin, essential oils, and pharmaceutical products and can be used for landscape reintegration. There are a number of potential turfgrass species that may be appropriate at various salinity levels of seawater. The goal of this review is to create greater awareness of salt-tolerant turfgrasses, their current and potential uses, and their potential use in developing countries. The future for irrigating turf may rely on the use of moderate- to high-salinity water and, in order to ensure that the turf system is sustainable, will rely on the use of salt-tolerant grasses and an improved knowledge of the effects of salinity on turfgrasses.